Analisis Penggunaan Istilah Di Dunia Teknologi Informasi Dalam Novel Romance Is Not For IT Folks Karya Ayu Welirang - Farih Al Kausar, Zidniy; Ega Prabowo, Julian; Dwi Kurniawan, Eva (Jurnal Manajemen, Ekonomi, Hukum, Kewirausahaan, Kesehatan, Pendidikan dan Informatika, 2023)
The novel entitled Romance is Not For IT Folks by Ayu Welirang is a literary work that discusses romance and social problems with the background of an IT employee. Therefore, this novel uses various terms in the world of information technology in assembling the narrative and supporting the story. This research was conducted with the aim of analyzing the use of these terms in the presentation of story narratives in the novel entitled Romance is Not For IT Folks by Ayu Welirang. The formulation of the problem in this research is how terms are used in the world of information technology in story development in the novel Romance is Not For IT Folks by Ayu Welirang. The method used in the analysis of the novel uses a hermeneutic approach to enable a deep understanding of the meaning and context of these terms. In this research the author explores several things related to the use of terms in the world of information technology in the novel Romance is Not For IT Folks by Ayu Welirang, including 1) Android and iOS, 2) API, 3) Bugs, 4) Fintech, 5) Full-stack Engineer, 6) Interface, 7) Server, 8) Start-up, and 9) Unicorn.